2021
DOI: 10.1016/j.heliyon.2021.e07319
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of challenges of crop production and marketing in Bench-Sheko, Kaffa, Sheka, and West-Omo zones of southwest Ethiopia

Abstract: This study was conducted to identify the challenges of crop production and marketing in southwest Ethiopia. Primary and secondary sources of data were used. Qualitative and Quantitative data types were collected from 385 respondents through interviews, focus group discussion, key informant interviews, and observations. The collected data were analyzed by using descriptive statistics and econometric models. Crop productivity was analyzed by the Cobb Douglas model and its efficiency and determinants were identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 28 publications
2
14
0
Order By: Relevance
“…The result has shown that about 28.10% of sampled household heads struggled with biotic factors which reduce tomato production. The result is similar to the findings of [15,34] who stated that more than 60% of the productivity of developing countries was lost due to biotic and abiotic factors.…”
Section: B Effect Of Socio-economics and Farm Tomato Productionsupporting
confidence: 90%
“…The result has shown that about 28.10% of sampled household heads struggled with biotic factors which reduce tomato production. The result is similar to the findings of [15,34] who stated that more than 60% of the productivity of developing countries was lost due to biotic and abiotic factors.…”
Section: B Effect Of Socio-economics and Farm Tomato Productionsupporting
confidence: 90%
“…However, large families require more significant amounts of food for sustenance, and the risk of food insecurity increases in subsistence farming where crop productivity is generally low. Tadele [52] noted that large families have an adverse impact on food security, especially in Africa, where the population growth rate is very high.…”
Section: Discussion 41 Demographic Attributesmentioning
confidence: 99%
“…Its carbohydrates richness, availability throughout the year, tolerance to low soil fertility, and resistance to drought, pests, and diseases (Mathende, 2006;Nassar, 2007;Fermont et al, 2008;van Fermont, 2009;Poole, 2010;McQuate, 2011;El-Sharkawy, 2012;Ogunniyi et al, 2012;Tadesse et al, 2017;Ewubare and Ologhadien, 2019;Inegbedion et al, 2020) make cassava an attractive crop, especially to smallholder farmers, who account for the largest share of the country's agricultural production. However, these farmers hardly use modern technology and inputs and hence their cassava productivity is low [Kebede et al, 2012;Laekemariam, 2016;Mustefa et al, 2017;Tadesse et al, 2021] despite significant market opportunities in Ethiopia [Biruk, 2013;Tadesse et al, 2013;Dada, 2016;Offa District Agricultural and Natural Resource Development Office (ODANRDO), 2018;Graffham et al, 2019]. Furthermore, empirical research on cassava economic efficiency (EE) in this specific region that will assist in identifying concrete improvement levers is scarce.…”
Section: Introductionmentioning
confidence: 99%